Islamophobia - Allen, Christoher (Ashgate Pub., 2010)
Allen begins by looking at ways of defining and understanding Islamophobia. He traces its historical evolution to the present day, considering the impact of recent events and their aftermath especially in the wake of the events of September 11, before trying to understand and comprehend a wider conception of the phenomenon.